Impact of coastal development on magrove distribution in Langkawi Island, Malaysia - Zuhairi Ahmad (Kulliyyah of Science, International Islamic University Malaysia, 2010)
This study investigates the impact of coastal development on mangrove distribution in Langkawi Island, Malaysia. The objectives of this study were to identify and determine type of coastal developments that affect mangrove cover, mangrove changes from 1995 to 2008, species distribution, and sediment characteristics in classified zone. Samplings were conducted throughout the islands, which involved groundtruthing for image classification, field observation and sediment samplings. SPOT images of Langkawi Island were analyzed using supervised classification and Principal Component Analysis (PCA). Sediment samples were analyzed using Particle Size Analyzer (PSA) through laser diffraction method. From the results, Langkawi mangroves in turn have degraded about 10.5% or 325.26 ha from its total area 3087.37 ha in 1996. In 2008, the total of Langkawi's mangroves available was 2762.11 ha which covered five major areas: Kilim River mangroves, Tuba Island mangroves, Dayang Bunting Island mangroves, Kuah mangroves and Teluk Ewa mangroves. Mangrove clearing is the major factor of mangrove degradation, which contributed 29% from total mangrove degraded area in Langkawi Island. These followed by mangrove conversion to residential and agriculture, which contributed 27% and 17% from total degraded area. As many as 30 mangroves species have identified with 25 species are included in exclusive category, 4 non-exclusive and 1 associate species. Mangroves sediment size ranges also affecting mangroves distribution and diversification. As one of the main tourism island in Malaysia, the pace of coastal developments in Langkawi Island had suppressed the mangroves for the past 20 years. Developments such as mangrove conversion to residential areas, commercial areas, agriculture plantations, aquaculture industries, facilities construction, and wake currents were involved mangrove clearing. Thus, monitoring mangroves changes was considered as essential in order to ensure its survival and sustainable. From this study, remote sensing and Geographic Information System (GIS) technology found to be reliable in monitoring large area and mapping the mangroves.